Танкист, или "Белый тигр": роман / И. В. Бояшов - Бояшов Илья Владимирович (Лимбус Пресс, 2008)
Экземпляры: АБ (20120903) / Инвентарный номер: 41093zzzzz / Цена: 440.59 / Сис.шифр: 84(2) / Авт.знак: Б 86 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)